Experiences of stigma and discrimination encountered by double orphaned children of Save in Chiredzi. - Dhundu, Confidence R. (Midlands State University, 2017)
The study sought to examine the experiences of stigma and discrimination encountered by double-orphaned children of Save in Chiredzi. The objectives of this particular study is to identify the psychosocial challenges encountered by double orphans of Save in Chiredzi both at home and at school, to find out if they receive support from their family, friends and the community and to determine how double-orphaned children cope up with the challenges they encounter and to recommend solutions in dealing with the experiences of stigma and discrimination challenges faced by these double-orphaned children. A phenomenological research design was used to describe the experiences of stigma and discrimination encountered by double-orphaned children and purposive sampling was used to select study participants. The sample was made up of 8 participants of which constituted 4 females and 4 males both from primary and secondary school. The age range of these participants was between 10-18 years. Data was collected using qualitative design where interviews were used as the main tool to collect data. Data was analysed using thematic analysis. Findings from the interviews of this study concluded that double-orphaned children encounter stigma and discrimination challenges and they are a vulnerable population to psychosocial challenges like stress, depression, low esteem, loneliness and discrimination drug abuse, exploitation and abuse. Double-orphaned children reported that they receive support from different sources of support which include social support, financial support, spiritual support and psychological support. Strategies used by double-orphaned children in coping with their psychosocial challenges include self-occupation, acceptance and future expectations. The researcher recommend the Government intervene and implement laws to challenge the stigmatisation and discriminatory attitudes towards double-orphaned children, FACT-Chiredzi support for double orphaned children in education, health, food security to promote social and economic support to improve stigma and discrimination encountered by double-orphaned children in rural communities.